Hypercortisolemic depressed women: lean but viscerally obese? - Deuschle, Michael; Gilles, Maria (Neuroendocrinology, 2015)
Background: Activation of the hypothalamic-pituitary-adrenal (HPA) system in depressed patients has been related to visceral adiposity. In contrast, low HPA system activity is associated with increased body fat in the general population. Our study intended to clarify whether HPA system activity is related to body weight and composition in depressed inpatients. Methods: In a cohort of 51 female and 20 male depressed inpatients, we measured saliva cortisol (HPA system activity), body mass index (BMI), waist circumference as well as body composition as reflected by bioimpedance. Results: In female patients, cortisol in saliva was negatively associated with fat-to-muscle ratio and BMI. Conclusion: In depressed inpatients, especially women, there is evidence that activation of the HPA system is related to relatively low body weight and low body fat content.